1984
DOI: 10.1007/bf00689339
|View full text |Cite
|
Sign up to set email alerts
|

Histoenzymological and ultrastructural study of a bifocal calcifying epithelial odontogenic tumor. characteristics of epithelial cells and histogenesis of amyloid-like material

Abstract: A calcifying epithelial odontogenic tumor, simultaneously located in the two jaws (maxilla and mandible) was examined by histochemical and electron microscopic methods. Squamous tumor cells without secretory polarity were different from those of common ameloblastoma. High activities of alkaline phosphatase and ATPases were demonstrated by light and electron microscopy on the cytoplasmic membrane, findings similar to those in the stratum intermedium cells of the normal dental germ from which these tumor cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Morimoto et al [1983] demonstrated ALP immunostain and enzyme activity associated with CEOT epithelial cell membranes. Additionally, high activities of ALP and ATPases were previously demonstrated by light and electron microscopy on the cytoplasmic membrane of a CEOT tumor, similar to findings in the stratum intermedium cells of the normal tooth germ from which these tumor cells are thought to arise [Chomette et al, 1984]. Our preliminary results suggest that ALP may be associated with the CEOT mineralization potential.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Morimoto et al [1983] demonstrated ALP immunostain and enzyme activity associated with CEOT epithelial cell membranes. Additionally, high activities of ALP and ATPases were previously demonstrated by light and electron microscopy on the cytoplasmic membrane of a CEOT tumor, similar to findings in the stratum intermedium cells of the normal tooth germ from which these tumor cells are thought to arise [Chomette et al, 1984]. Our preliminary results suggest that ALP may be associated with the CEOT mineralization potential.…”
Section: Discussionsupporting
confidence: 62%
“…Several reports have emphasized that CEOTs have obvious mineralization features such as nodular deposition of congophilic amyloidlike material with partial mineralization [Kang et al, 2006]. This pseudo-amyloid substance is thought to represent abnormal EMPs associated with mineralization [Chomette et al, 1984]. Our study found higher expression levels of ALP in CEOT-1 compared to AB-1 and KCOT-1.…”
Section: Discussionsupporting
confidence: 62%
“…Most investigators are of the opinion that it arises from stratum intermedium as tumor cells are morphologically similar and possess a high alkaline phosphatase and adenosine triphosphate activity. 5 Other possible considerations for the cell of origin are from oral epithelium, dental lamina or its remnants, and reduced enamel epithelium. 2 The CEOT shows three important histological features.…”
Section: Discussionmentioning
confidence: 99%
“…Small, intrabony mandibular lesions with well-defined borders are treated by simple enucleation or curettage followed by judicious removal of a thin layer of bone adjacent to the tumor. 5 Large tumors require aggressive approach by segmental resection, hemimandibulectomy and hemimaxillectomy, which cause bone discontinuity requiring reconstruction procedures, such as grafting or distraction osteogenesis. 7 Recurrence rate of 10 to 20% following conservative treatment is reported.…”
Section: Treatmentmentioning
confidence: 99%
“…[35] This idea is based on the morphological similarity of the tumor cells to the normal cells of stratum intermedium and a high activity of alkaline phosphatase and adenosine triphosphate. [6] It has been suggested that amyloid deposition within Pindborg tumor is an immunologic response to these stratum intermedium cells. Others insist that it arises from remnants of the primitive dental lamina found in the initial stage of odontogenesis, and these epithelial rests are the more likely true progenitor cell.…”
Section: Discussionmentioning
confidence: 99%